PENGARUH EFISIENSI MODAL KERJA DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PT. SIERAD PRODUCE TBK TAHUN 2007-2014 - Lita Wulantika; Fitri Amalia (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2014)
ABSTRACTEach company will perform various activities for achieving the goals set. Efficient fund management will causes the maximum profit. In addition to the effective working capital funds management, in obtaining profitability the company also needs pay attention to likuidity.The direction of this research is for identify and explain effect of working capital management (WCT) and liquidity (CR) to profitability at Sierad Produce Tbk. period 2007-2014 listed on the stock exchange Indonesia. The analitical tool used in this research is using path analysis. The sampel used is quarter time series data during 8 periods as many as 32 financial statement report.Result of path analysis showing that working capital management and liquidity significantly effect to profitability. Amount of adjusted R-squared is 0,428 which mean profitability (ROI) being able to explain by independent variabel researched at 42,8% and remaining 57,2% affected by variabel not examined in this researched.Keyword : working capital management, liquidity, profitability